The definition and diagnosis of cold hypersensitivity in the hands and feet: Finding from the experts survey - Kwang-Ho Bae; Young-Seok Jeong; Ho-Yeon Go; Seung-Ho Sun; Tae-Hoon Kim; Ki-Yong Jung; Yun-Kyung Song; Seong-Gyu Ko; You-Kyung Choi; Jong-Hyeong Park; Siwoo Lee; Youngseop Lee; et al. (Integrative Medicine Research)
Background: Cold hypersensitivity in the hands and feet (CHHF) is a symptom patients usually feel cold in their hands and feet, but not dealt with a disease in western medicine. However, it is often appealed by patients at a clinic of Korean medicine (KM), considered to be a sort of key diagnostic indicator, and actively treated by physicians. Nevertheless, there is no standardized diagnostic definition for CHHF. Therefore, we surveyed KM experts’ opinions to address the clinical definition, diagnostic criteria, and other relevant things on CHHF. Methods: We developed a survey to assess the definition, diagnosis, causes, and accompanying symptoms on CHHF. 31 experts who work at specialized university hospitals affiliated with KM hospitals consented to participation. Experts responded to survey questions by selecting multiple-choice answers or stating their opinions. Results: Vast majority of experts (83.8%) agreed with our definition on CHHF (“a feeling of cold as a symptom; that one's hands or feet become colder than those of average people in temperatures that are not normally perceived as cold”). 77.4% of experts considered subjective symptoms on CHHF were more important than medical instrument results. Constitution or genetic factors (87.1%) and stress (64.5%) were the most common causes reported for CHHF. Conclusions: This study offers an expert consensus regarding the themes, opinions, and experiences of practitioners with CHHF. Our results underscore the need for standardized definitions and diagnostic criteria for CHHF. Keywords: Cold hypersensitivity, Cold extremities, Cold constitution